2020
DOI: 10.1038/s41598-020-77375-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of MADS-box gene family revealed its role in vegetative development and stem ripening in S. spontaneum

Abstract: Sugarcane is the most important sugar and biofuel crop. MADS-box genes encode transcription factors that are involved in developmental control and signal transduction in plants. Systematic analyses of MADS-box genes have been reported in many plant species, but its identification and characterization were not possible until a reference genome of autotetraploid wild type sugarcane specie, Saccharum spontaneum is available recently. We identified 182 MADS-box sequences in the S. spontaneum genome, which were ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
1
11
1
Order By: Relevance
“…A better understanding of this family in terms of their member feature, structure characteristics can provide new ideas for further functional analysis. Compared with previous studies, the number of this family member varies in different species, with 107 in Arabidopsis [18], 105 in populus trichocarpa [19], 48 in pineapple [20], 182 in Saccharum spontaneum [21], 44 in Erigeron breviscapus [19,22], 64 in Salix suchowensis [43]. A total of 69 MADS-box proteins were identified from the coco tree in this study (Table 1), which is less than that in Arabidopsis.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A better understanding of this family in terms of their member feature, structure characteristics can provide new ideas for further functional analysis. Compared with previous studies, the number of this family member varies in different species, with 107 in Arabidopsis [18], 105 in populus trichocarpa [19], 48 in pineapple [20], 182 in Saccharum spontaneum [21], 44 in Erigeron breviscapus [19,22], 64 in Salix suchowensis [43]. A total of 69 MADS-box proteins were identified from the coco tree in this study (Table 1), which is less than that in Arabidopsis.…”
Section: Discussioncontrasting
confidence: 59%
“…Although MADS-box genes are well-known for their roles in the flower developmental process and participating in the classical ABC flower development model, some of them have been validated to function on root and leaf morphogenesis [16,17]. To date, the MADS-box proteins have been characterized in various kinds of plants, including Arabidopsis [18], Populus trichocarpa [19], pineapple [20], Saccharum spontaneum [21], Erigeron breviscapus [22]. However, little is known regarding the MADS-box gene family in Theobroma cacao.…”
Section: Introductionmentioning
confidence: 99%
“…The NAC gene group (NAM, ATAF, and CUC) is one of the largest plant-specific TF families involved in plant development, stress responses [50] and plant immune responses [51]. Similarly, members of the MADS-box gene family are involved in developmental control, signal transduction, and stress responses in various plants [52,53]. Because TFs function to regulate the expression of multiple target genes, their loss or gain of function can lead to dramatic phenotypic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression SHATTERPROOF 2 ( IiSHP2 ) from Isatis indigotica produced shortened sepals that cannot completely encapsulate the flower buds in transgenic Arabidopsis [ 27 ]. These previous results suggested that some MADS-box genes have diverse roles in both vegetative and reproductive development [ 26 , 28 , 29 ]. However, their regulation mechanism need further analysis.…”
Section: Introductionmentioning
confidence: 91%
“…Another MADS-box gene ( POTM1 ) from potato specifically accumulates in vegetative growth meristem and regulates the formation of axillary buds [ 25 ]. In sugarcane, SOC1 and SHORT VEGETATIVE PHASE ( SVP ) mainly regulate vegetative growth and are detected in leaves, roots, and stems [ 26 ]. Overexpression SHATTERPROOF 2 ( IiSHP2 ) from Isatis indigotica produced shortened sepals that cannot completely encapsulate the flower buds in transgenic Arabidopsis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%